The role of segmental speckle tracking echocardiography in characterising right ventricle dilation patterns: a multicentre study on healthy adolescent athletes. (4th February 2022) - Dorobantu, D; Riding, N; Mcclean, G; Sanz De La Garza, M; Abuli Luch, M; Adamuz, C; Ryding, D; Perry, D; Mcnally, S; Stuart, AG; Sitges, M; Oxborough, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): UK Research and Innovation - Medical Research Council GW4 Studentship Background: Right ventricle inflow (RV) dilation is a common adaptation to training in professional athletes, but how this impacts myocardial mechanics is yet unclear. Previous studies in athletes have found changes in segmental longitudinal strain (Sl), namely mid segment Sl, compared to normal controls, and have proposed RV dilation as a possible explanation. Whether different patterns of RV dilation are found in athletes, and if these influence regional RV mechanics is not known. Purpose: To describe the patterns of RV dilation in healthy adolescent athletes and their relationship to segmental myocardial mechanics. Methods: A total of 346 healthy athletes (<18 years) screened at 3 sports academies between 2014 and 2019 with measurements for RV Sl, RV basal and RV apical diameters were included. Four groups were defined based on the basal and apical RV diameters size relative to the whole group distribution: No RV dilation (both basal and apical RV diameter under the 25th percentile), basal dilation (only basal RV above the 75th percentile), apical dilation (only apical RV above the 75th percentile) and global dilation (both the basal and apical RV above the 75th percentile). The segmental Sl was compared between the groups using a one-way ANOVA test with Bonferroni correction. Results: The mean (SD) age was 14.5 (1.6) years, with athletes coming from various ethnic (55% arab, 22% white and 22% black) and sports backgrounds (75% mixed, 11% power, 8% endurance and 6% skill). Based on the RV diameters, the following groups were defined: no dilation (n = 35), basal dilation (n = 53), apical dilation (n = 51) and global dilation (n = 33). There were variations in dilation pattern by ethnicity and practised sports (Figure 1). RV free wall Sl was less negative ("lower") in the apical and global dilation groups compared to the no dilation group (-26.7% and -26.4% vs -28.6%, p = 0.04 and 0.03, respectively). Mid segment Sl was consistently lower in all 3 dilation pattern groups, compared to the no dilation group (Figure 2, *denotes p < 0.05). Basal Sl was lower in the global dilation group compared to those with no dilation (p = 0.05). There were also differences between the basal and apical dilation groups: basal Sl was lower (p = 0.01) and apical Sl higher (p = 0.02) the apical dilation group. Conclusions: RV dilation in healthy athletes can be global, predominately basal or predominately apical. Apical and global dilation were more prevalent in non-white ethnicity, endurance and power sports. Lower mid segment Sl values were observed in all 3 dilation patterns, but FW Sl was only lower in the apical and global dilation groups. This suggests that there are different patterns of RV remodelling in athletes, which can be further characterised using segmental strain analysis.